Narrow‐Bandgap Chalcogenoviologens for Electrochromism and Visible‐Light‐Driven Hydrogen Evolution. (23rd March 2018) - Li, Guoping; Xu, Letian; Zhang, Weidong; Zhou, Kun; Ding, Yousong; Liu, Fenglin; He, Xiaoming; He, Gang
Abstract: A series of electron‐accepting chalcogen‐bridged viologens with narrow HOMO–LUMO bandgaps and low LUMO levels is reported. The optoelectronic properties of chalcogenoviologens can be readily tuned through heavy atom substitution (S, Se and Te). Herein, in situ electrochemical spectroscopy was performed on the proof‐of‐concept electrochromic devices (ECD). E‐BnV 2+ (E=Se, Te; BnV 2+ =benzyl viologen) was used for the visible‐light‐driven hydrogen evolution due to the strong visible‐light absorption. Remarkably, E‐BnV 2+ was not only used as a photosensitizer, but also as an electron mediator, providing a new strategy to explore photocatalysts. The higher apparent quantum yield of Se‐BnV 2+ could be interpreted in terms of different energy levels, faster electron‐transfer rates and faster formation of radical species.